Womanpriest Tradition and Transgression in the Contemporary Roman Catholic Church - PETERFESO, JILL (Catholic Practice in North America, 2020)
"This book is openly available in digital formats thanks to a generous grant from the Andrew W. Mellon Foundation. While some Catholics and even non-Catholics today are asking if priests are necessary, especially given the ongoing sex-abuse scandal, The Roman Catholic Womanpriests (RCWP) looks to reframe and reform Roman Catholic priesthood, starting with ordained women. Womanpriest is the first academic study of the RCWP movement. As an ethnography, Womanpriest analyzes the womenpriests' actions and lived theologies in order to explore ongoing tensions in Roman Catholicism around gender and sexuality, priestly authority, and religious change. In order to understand how womenpriests navigate tradition and transgression, this study situates RCWP within post-Vatican II Catholicism, apostolic succession, sacraments, ministerial action, and questions of embodiment. Womanpriest reveals RCWP to be a discrete religious movement in a distinct religious moment, with a small group of tenacious women defying the Catholic patriarchy, taking on the priestly role, and demanding reconsideration of Roman Catholic tradition. Doing so, the women inhabit and re-create the central tensions in Catholicism today."